Opportunities and Challenges for Traditional Chinese Medicine in South Asia under the “Belt and Road” Initiative: The Case of Nepal and Pakistan - Yang, Chunxue; Zhou, Xinmei; Ma, Xinyu; Zhao, Zhiling (Khwopa Journal, 2024)
Driven by the Belt and Road Initiative (BRI), China is quickly expanding its cooperation and integration with other nations worldwide, particularly in South Asia, across a range of sectors. The present study examines how the BRI has contributed to the globalization of traditional medicine, particularly in South Asia. South Asia’s culture is more open to Traditional Chinese Medicine (TCM) because it values conventional medical practices. This article examines the opportunities and difficulties of TCM cooperation between Nepal and Pakistan using those two nations as case studies. Furthermore, the article addresses methods to improve TCM’s worldwide distribution and long-term growth. Despite the challenges and concerns, the Belt and Road Initiative presents a unique opportunity to enhance regional connectivity via international cooperation and opens up new channels for the international promotion of Traditional Chinese Medicine.